Evaluasi Keberhasilan dan Penerimaan Sistem Akuntansi Instansi Berbasis Akrual di Komisi Pemilihan Umum - Damayanthi, Kadek Shintya Rahayu Dewi; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 32 No 4 (2022), 2022)
This study aims to test the success and acceptance of the Accrual-Based Agency Accounting System (SAIBA) by using an integration evaluation model from the combination of the UTAUT, Delone and McLean, and HOT-Fit models. The ten information variables used in this study are business expectancy, social influence, system quality, service quality, environment or service quality, interest, and net benefits. The population in this study were all users of SAIBA. Determining the research sample using all members of the population, namely the saturated sample by distributing questionnaires to 50 people from 10 work units within the General Election Commission in Bali Province. Hypothesis testing using Partial Least Square. The results showed that performance expectancy, business expectancy, social factors, information quality, system quality, and organizational environment had a positive effect on interest in using SAIBA. However, the quality of services and facilities has no effect on the interest in using SAIBA. Usage interest has a positive effect on net profit. Keywords: Success; Acceptance; SAIBA; Net Benefits.